Nurses' comfort care of transarterial chemoembolization patients based on their perceptions around postembolization syndrome and symptom interference - Myoung Soo Kim; Minkyeong Kang; Jiwon Park; Jung Mi Ryu (Wiley, 2023)
Abstract Aim Post‐embolization syndrome is a common adverse event following trans‐arterial chemoembolization, which negatively impacts the daily life of the patients involved. This study examined whether perceptions around post‐embolization syndrome and symptom interference among nurses affect their comfort care performance toward patients who have undergone this procedure. Design A descriptive cross‐sectional study. Methods One hundred and fifty registered nurses were surveyed from September to November 2020. Perceived post‐embolization syndrome, symptom interference, and comfort care (including physical, psychospiritual, sociocultural, and environmental dimensions) were measured. Data were analyzed using t‐tests, analysis of variance, Pearson's correlation, and a multivariate analysis of variance. Results There were no individual effects found of perceived post‐embolization syndrome or symptom interference on nurses' comfort care performance. However, statistically significant interaction effects were found in terms of their sociocultural and environmental care. Conclusion Nurses who recognized both high post‐embolization syndrome and symptom interference among their patients were found to provide greater sociocultural and environmental care. As such, nurses should improve their early symptom and symptom interference detection protocols based on current care guidelines and provide physical, psychospiritual, sociocultural, and environmental comfort care.